2007
DOI: 10.1111/j.1365-2591.2007.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible but not reversible pulpitis is associated with up‐regulation of tumour necrosis factor‐alpha gene expression in human pulp

Abstract: Kokkas AB, Goulas A, Varsamidis K, Mirtsou V, Tziafas D.Irreversible but not reversible pulpitis is associated with up-regulation of tumour necrosis factor-alpha gene expression in human pulp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 23 publications
4
57
1
2
Order By: Relevance
“…During the treatment of a deep carious lesion, a clinician must decide whether the pulpal inflammation is reversible or irreversible based on subjective findings (4), and therefore objective analysis of pulpal cytokine levels can provide useful information about pulpal pathology. Several cytokines have been suggested to be indicators of inflammation (8,(10)(11). In the present study, comparison of the cytokine levels in mechanically and cariously exposed pulp was able to provide a clearer picture of pulp status at the time of treatment.…”
Section: Discussionmentioning
confidence: 57%
“…During the treatment of a deep carious lesion, a clinician must decide whether the pulpal inflammation is reversible or irreversible based on subjective findings (4), and therefore objective analysis of pulpal cytokine levels can provide useful information about pulpal pathology. Several cytokines have been suggested to be indicators of inflammation (8,(10)(11). In the present study, comparison of the cytokine levels in mechanically and cariously exposed pulp was able to provide a clearer picture of pulp status at the time of treatment.…”
Section: Discussionmentioning
confidence: 57%
“…As might be expected, our experiments showed that TNF‐α depressed the expression of Panx3 in a dose‐dependent manner. TNF‐α, both trauma and bacteria could induce its secretion, act as a pro‐inflammatory cytokine and aggravate inflammatory response, then ultimately initiate dental pulp inflammation and pain 10, 11, 12, 13, 24. Previous studies have reported that TNF‐α could suppress the expression of several hemichannels in various cell types 25, 26, 27.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of TNF-α have been detected in patients with pulpitis (Pezelj-Ribaric et al 2002;Kokkas et al 2007). We first sought to reaffirm whether patients with tooth decay exhibit increased expression of TNF-α.…”
Section: Development Of a Mouse Model For Conditional Overexpression mentioning
confidence: 99%
“…Elevated levels of TNF-α have often been detected in the serum and tissues of patients with severe infections or autoimmune disorders. For example, upregulation of TNF-α has been discovered in pulpal tissues from teeth with irreversible pulpitis (Pezelj-Ribaric et al 2002;Kokkas et al 2007) and in exudates of teeth with apical periodontitis (Safavi and Rossomando 1991). In addition to being proinflammatory, TNF-α may act directly on nociceptive neurons to increase pain sensitivity.…”
Section: Introductionmentioning
confidence: 99%